2004
DOI: 10.4102/jsava.v75i3.467
|View full text |Cite
|
Sign up to set email alerts
|

The use of a bacterin vaccine in broiler breeders for the control of Ornithobacterium rhinotracheale in commercial broilers

Abstract: <em>Ornithobacterium rhinotracheale</em> (ORT) is a recently identified bacterial pathogen of poultry, linked to the respiratory disease complex of broilers and the economic losses associated with that disease complex. Present control measures applied for the disease include the continuous use of in-feed antibiotics. A recently developed bacterin vaccine that is applied to broiler-breeder hens to pass on protective immunity to their broiler progeny was tested under large-scale commercial conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Thus, knowledge about the host immune response is of great importance for the development of more effective vaccines [86]. Different vaccines, including recombinant ones, have been developed and reported with variable results for the control of both natural and experimental ORT infections [74,85,[87][88][89][90][91].…”
Section: Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, knowledge about the host immune response is of great importance for the development of more effective vaccines [86]. Different vaccines, including recombinant ones, have been developed and reported with variable results for the control of both natural and experimental ORT infections [74,85,[87][88][89][90][91].…”
Section: Vaccinationmentioning
confidence: 99%
“…In experimental challenges using inactivated vaccines, it was possible to obtain high maternal antibody titers in chicken matrices, resulting in sufficient progeny protection [74,87,89]. Cauwerts et al [74] also achieved lower mortality rates and higher average production indices in progenies from vaccinated matrices.…”
Section: Vaccinationmentioning
confidence: 99%
“…The birds suffered sneezing, associated with increased mortality and poor performance parameters. At postmortem examination, pneumonia and foamy white and "yoghurt-like" exudate were observed in the abdominal air sacs and the bacteriological study revealed a slow growing, pleomorphic, Gram-negative rod unknown among the bacterial species previously reported (van Empel, 1998;van Empel and Hafez, 1999;Bisshop, 2003). A bacterium similar to Pasteurella spp.…”
Section: Historymentioning
confidence: 79%
“…causing enough protection in the progeny against experimental challenges (van Empel and van den Bosch, 1998;Cauwerts et al, 2002;Bisshop, 2003). In addition, Cauwerts et al (2002) found lower condemnation rates, lower mean mortality and higher mean production index in the progeny from vaccinated broiler breeders.…”
Section: Vaccinationmentioning
confidence: 92%
See 1 more Smart Citation